Lethal Organ Donation: Would the Doctor Intend the Donor's Death?. Issue 4 (29th July 2019) - Bronner, Ben
Abstract: Lethal organ donation is a hypothetical procedure in which vital organs are removed from living donors, resulting in their death. An important objection to lethal organ donation is that it would infringe the prohibition on doctors intentionally causing the death of patients. I present a series of arguments intended to undermine this objection. In a case of lethal organ donation, the donor's death is merely foreseen, and not intended.